A reflective study on Indonesian English teacher’s expectation from teacher forum for professional development - Sueb Sueb; Ririn Pusparini; Anis Trisusana; Esti Kurniasih; Nur Chakim (Universitas Islam Malang, 2020)
Teacher professional development is an ongoing process. Standing on the frontline in implementing educational policies, teachers are encouraged to actualize both theoretically, policies, and practices. One way to improve the professionalism of a teacher is reflection through an academic forum so as to enrich the inquiry obtained in order to improve individual professionalism. This is an ongoing research involving English teachers in East Java members of the ELT Best Practices academic forum. The goal is to elaborate two basic things, namely the motivation of teachers in their involvement in academic forums and how academic forums can help them in conducting self-reflection in order to increase professionalism. Almost all teachers say that increasing professionalism as an English teacher is the main motivation. In detail, several aspects that are the focus of improvement are language skills, teaching techniques, the renewal of language teaching theories, and increasing networking among English teacher professions. With diverse backgrounds ranging from English teachers in middle and high school (or similar), the academic forum is considered important to help the teachers upgrade their knowledge and professionalism.